Hemoglobin decline, function, and mortality in the elderly: The cardiovascular health study1. Issue 1 (9th October 2012) - Zakai, Neil A.; French, Benjamin; Arnold, Alice M.; Newman, Anne B.; Fried, Linda F.; Robbins, John; Chaves, Paulo; Cushman, Mary
Abstract While anemia is associated with poor functional and mortality outcomes in the elderly, the impact of hemoglobin decline is less studied. We evaluated the determinants and consequences of hemoglobin decline in 3, 758 non‐anemic participants from the Cardiovascular Health Study, a prospective cohort of community‐dwelling elderly ≥65 years old at baseline and followed for up to 16 years. Hemoglobin was measured at baseline and 3 years later and anemia defined by World Health Organization (WHO) criteria. We modeled hemoglobin decline in two ways: (1) per each 1 g/dL decrease in hemoglobin and (2) development of anemia by the WHO criteria. Among participants without baseline anemia, hemoglobin decreased by 0.4 g/dL and 9% developed anemia over 3 years. Baseline increasing age, female sex, diabetes, and kidney disease predicted hemoglobin decline over 3 years. Baseline increasing age, being African‐American, and kidney disease predicted anemia development over 3 years. Hemoglobin decline was associated with subsequent worse cognitive function in men and anemia development with subsequent worse cognitive function in women. Both anemia development (HR 1.39, 95% CI 1.15, 1.69) and hemoglobin decline (HR 1.11, 95% CI 1.04, 1.18 per 1 g/dL decrease) predicted subsequent mortality in men and women. Hemoglobin decreases identified a large group of elderly individuals at risk for subsequent adverse outcomes who would not be identified using the WHO anemia criteria. These data may allow clinicians to identify at‐risk elderly individuals for early intervention to improve the quality and quantity of life. Am. J. Hematol. 2013. © 2012 Wiley Periodicals, Inc.